Pengembangan Sistem Manajemen Perusahaan Roti berbasis Website (Studi Kasus: CV Roti Langsung Enak) - Maulidiya Qurrota Ayun; Achmad Arwan; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In a company, the process of managing production and the product delivery is one of the most important processes that have a big impact. Companies must arrange how to manage production, record production stock, and arrange how to distribute a product. these factors can affect how to managing productivity to be more efficient. CV Roti Langsung Enak is one of the bakeries in Sumbawa. CV Roti Langsung Enak, on average it produces 800 to 1000 loaves of bread each day. During its development, the bakery began to experience several problems, such as bread returns, where the number of bread returns caused a considerable loss to the bread company. Therefore a website-based bread company management system was created that can help manage the bread production process to minimize bread returns. This system is also able to help the process of ordering bread and delivering bread to make it more effective and efficient. This system uses the waterfall method to make it more structured and sequential for each step taken. From the requirement analysis process, there are 3 actors, 30 functional needs, and 1 non-functional requirement. The tests used to test this system are unit testing, integration testing, validation testing, and compatibility. Tests carried out proves that the system is able to run as expected and able to be run on various browsers and devices.